Amephana dalmatica (Rebel, 1919) (Lepidoptera: Noctuidae) found in the Nature Park “Golija”: A new species in the fauna of the Republic of Serbia - Stojanović Dејаn V. (Zbornik Matice Srpske za Prirodne Nauke)
Inventorying the diversity of entomofauna is the first stage in a consistent approach to its conservation. The diversity of Lepidoptera in Serbia, although impressive in terms of the number of inventoried species, is far from complete. This paper describes the first finding of the species Amephana dalmatica (Rebel, 1919) in the Republic of Serbia. Moreover, for the first time, a species from the genus Amephana Hampson, 1906 is recorded in the fauna of Lepidoptera of Serbia. A. dalmatica is a Ponto-Mediterranean species. It occurs in the Southern Europe (western and southern parts of the Balkans, north to Dalmatia), as well as in the western and southwestern parts of European Turkey. Here are presented the basic anatomical-morphological and taxonomic characteristics of the species A. dalmatica, its distribution and flight period. The three out of the eight research objectives on the Lepidoptera fauna in the Republic of Serbia were implemented in this research, presented in the “General Plan of Lepidopterological Research for the Achievement of Defined Goals in the Republic of Serbia with a Focus on Climate Change, Allochthonous and Migratory Species”: Golija is one of the highest mountains in the Republic of Serbia, it is a protected area and A. dalmatica is a rare Lepidoptera species in the Republic of Serbia, which speaks of the importance of this study and the research area.